ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PASAR TANAH NON PERUMAHAN DI KAWASAN PERKOTAAN YOGYAKARTA (KPY) KABUPATEN SLEMAN, DAERAH ISTIMEWA YOGYAKARTA - , M. IMAM BINTORO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine factors that affect the value of non-residential market in Kawasan Perkotaan Yogyakarta (KPY), Sleman, Yogyakarta. Sleman district selected in this study because of Sleman Regency is an area that is experiencing the fastest increase in the real estate business compared to other districts in the province of Yogyakarta (DIY) This study uses descriptive and multiple regression analysis with panel data that combines observation unit at the same time/time series and cross section. Assuming there are no specific components both in cross section and time sequence, the regression equation is estimated using panel data methods with Ordinary Least Squares. The results of this study indicate that that the value of land in the district of Depok on average have the highest value among the five other districts, followed Ngaglik, Gamping, Sleman, District Mlati and Ngemplak. In addition, factors that generally affect the market value of non-residential sub-district in the district under the Sleman regency are vast land (subdistrict Depok), the width of the road (District of Gamping, Mlati, Sleman, Depok, Ngaglik), distance to business center (District of Gamping, Mlati, Sleman, Depok, Ngemplak). Overall, the general factors that vast land, road width and distance from the CBD is consistent with other studies are all factors that affect the value of non-residential land in KPY Sleman Regency. Contribution of this study is to provide input to the appraiser in using the vast land, the width of the road and the distance to the CBD as important items in making adjustmentat the time of valuation of land in Sleman regency. This study is also useful for developers who chose the location in a residential district to pay attention to the factors of vast land, the width of the road and the distance to the CBD at the time of choosing the land to be developed. In addition, the results of this study also provide input for local governments to consider the influence of land area, the width of the road and the distance to the CBD in determining the tax land. Keywords : Land value, vast land, the width of the road, distance to the CBD